The past at risk: assessing climate and geological hazard for the preservation of archaeological sites in coastal Peru using open-access data - Mauricio, Ana Cecilia; Fernandini, Francesca (Frontiers in Environmental Archaeology, 2026)
The immovable archaeological heritage of Peru is among the richest in the world, particularly along the Peruvian coast, which boasts numerous examples dating from the Terminal Pleistocene to the Inca times (13000 BP-1532 AD). This cultural heritage is an important source of scientific and historical information, is the source for the construction of national identity(ies) and contributes significantly to the social and economic development of the surrounding communities. However, this archaeological heritage is under constant threat of destruction due to various factors, including climate change and human activities. This paper outlines the results of a multidisciplinary research conducted on the Peruvian coast, aimed at identifying the most significant geological and climatic hazards affecting the preservation of coastal archaeological sites. Based on fieldwork conducted on the northern and central coast, a low-cost, primarily remote analysis methodology was developed. This methodology utilizes open-access geological, cultural, archaeological, and climatic data, geographic information system, and aerial imagery to identify the effects of climatic risk (particularly El Niño), geological hazards, and to assess the vulnerability of archaeological sites to these hazards. This methodology, which provides updated and multi-variable data, is designed to support local and regional authorities in decision-making processes related to the planning and preservation of Peru's pre-Hispanic cultural heritage.